Soundscape studies and cultural geography (1971-2020) (2022)
In this paper, we carry out a descriptive analysis of the historical conceptual development of soundscape. The aim is to identify how a study environment has been built around this proposal. We developed a selective search of the literature, starting with key texts by Murray Schafer and the World Soundscape Project, from which we traced its influence in different parts of the world. A period of expansion was identified during the 1980s, in which its two main approaches were shaped: the ecological and the perceptional-cultural. Likewise, special emphasis was placed on how the term was approached from the culturalist perspective in geography, and it was identified that from these discussions arose the proposal of auditive geographies and sound geographies. Finally, a systematic review was carried out in indexes and search engines of academic literature and we found a latent interest, during the last fifteen years, in incorporating sound as an objective of study from some of the positions mentioned (soundscape, auditive geographies, and sound geographies), however, it is a topic that is still in the process of consolidation.